2003
DOI: 10.1016/s1010-7940(03)00520-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of tourniquet occlusion and intraluminal shunts in beating heart surgery

Abstract: The intimal lesions observed after tourniquet occlusion in our experimental off-pump surgery model confirmed other recent studies. In contrast, utilization of TILS caused only minor damage of the vessel wall. The endothelial abrasions detected in this group may be a consequence of micro-dislocations or insertion maneuvers. Chronic studies are necessary to verify as to whether the mild injury after TILS insertion will result in a reduction or even absence of de-novo stenoses compared with tourniquet occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Clinical and histopathological safety of TICS is controversial. There are some reports advocating for TICS [7,18,19]. In a porcine model, Wipperman et al recommended the use of TICS instead of external occlusion devices based on acute and chronic vascular changes [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical and histopathological safety of TICS is controversial. There are some reports advocating for TICS [7,18,19]. In a porcine model, Wipperman et al recommended the use of TICS instead of external occlusion devices based on acute and chronic vascular changes [13].…”
Section: Discussionmentioning
confidence: 99%
“…New cut slides were stained histochemically with AgNO3 and immunohistochemically with CD31 (JC70A; DAKO, Denmark), which, along with HE slides, gave better information about the changes in the vascular structure. The endothelial and coronary wall damages were graded as follows: grade 0: characteristic injuries not found; grade 1: isolated existing; grade 2: usually existing; grade 3: always existing, according to Wippermann et al [7]. In addition to evaluation of vascular damage, presence of intimal hyperplasia and denudation were also noted.…”
Section: Histopathological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Wippermann et al have shown in an animal study that intraluminal shunts cause only moderate trauma to the vessel and may therefore be superior regarding acute and chronic intimal integrity in contrast to tournique occlusion [11,12]. In contrast, some investigators revealed that intracoronary shunts might create a greater degree of endothelial dysfunction compared to extravascular devices such as bulldog clamps or double-looped Gore-Tex suture snaring.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and histopathological safety of tournique occlusion or intraluminal shunt technique remains controversial [11-15]. The aim of this study was to evaluate the benefit of intraluminal-LAD shunt on myocardial damage in MIDCAB patients.…”
Section: Introductionmentioning
confidence: 99%